Anxiety and Depression in Cyberbullied College Students: A Retrospective Study - Jenaro, Cristina (Journal of interpersonal violence, 2021)
Cyberbullying is a worldwide phenomenon and its effects can be severe. To better understand the personal and situational factors in cyberbullying, we approach it from the perspective of the general aggression model. More specifically, we analyze the medium and long-term impact of past experiences of cyberbullying on university students. We also compare their psychological adjustment with peers who have not been cyberbullied by examining the recall of cyberbullying while attending secondary school of 1,593 university students. Participants from a Spanish University (N = 680) and a Bolivian University (N = 913) were invited to participate by filling in an online survey. It included the School Violence Questionnaire-Revised, CUVE-R, to assess school and classroom climate in relation to bullying and cyberbullying, the Beck Depression Inventory, and the State-Trait Anxiety Inventory. Results show that among the participants, 5.1% reported having suffered cyberbullying and 19.3% reported having been a bystander of cyberbullying, with similar percentages between universities. Canonical correlation suggests that variables related to school climate best explain the variability among participants who have and have not been cyberbullied. Those who have been cyberbullied scored significantly higher on anxiety and depression symptoms as well. Being a bystander of cyberbullying was not associated to significant differences on psychological adjustment (i.e., anxiety and depression). Results indicated that experiencing cyberbullying in secondary school is associated to lower psychological adjustment years later as university students. School climate variables contribute more strongly to identifying victims of cyberbullying. These results support the need for psychosocial interventions from a broader perspective, addressing the different dimensions of this phenomenon and its impact on victims.